Ammonia Blood Levels and Valproic Acid - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The prevalence and magnitude of valproic acid (VPA)-related hyperammonemia (HA) were estimated by a review of the literature, and the clinical symptomatology and risk factors for the development of HA determined by researchers at university hospitals in Santiago, Chile; and Rush University Medical Center, Chicago, IL.